Students' Satisfaction on Social Media Platforms of Tribhuvan University in Nepal - Thapa, Bhim Kumar (DEPAN, 2023)
This study examines the Perceived Ease of Use (PEOU), Usefulness (PU), and Risk of Social Media (SM) platforms affect Tribhuvan University students' Satisfaction (SS). Descriptive and analytical research design is utilized employing primary data analysis. The research investigates the impact of these factors on students’ satisfaction. According to the findings, there is a substantial positive link between SS with PEOU and PU of social media. This suggests that satisfaction rises in tandem with perceived usefulness and ease of use. There is less of a link between Perceived Risk and Students’ Satisfaction. PR does not show up as a major predictor, despite regression analysis's additional confirmation of the perceived usefulness and simplicity of use's strong predictive effect on satisfaction. These results add to our knowledge of the variables affecting how students see social media sites and provide insightful information that can be used to improve user happiness in learning environments. By using these data, administrators and faculties may create more successful plans for incorporating social media into the classroom, which will improve students' entire educational experience